1995
DOI: 10.1128/aac.39.10.2248
|View full text |Cite
|
Sign up to set email alerts
|

Role of mutations in DNA gyrase genes in ciprofloxacin resistance of Pseudomonas aeruginosa susceptible or resistant to imipenem

Abstract: In Pseudomonas aeruginosa, resistance to imipenem is mainly related to a lack of protein OprD and resistance to fluoroquinolones is mainly related to alterations in DNA gyrase. However, strains cross resistant to fluoroquinolones and imipenem have been selected in vitro and in vivo with fluoroquinolones. We investigated the mechanisms of resistance to fluoroquinolones in 30 clinical strains of P. aeruginosa resistant to ciprofloxacin (mean MIC, >8 g/ml), 20 of which were also resistant to imipenem (mean MIC, >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…1A. In accordance with the findings of several previous studies (25,26,27,28,29,30,31), the most frequently observed mutation, T83I, was encoded in the QRDR of gyrA, whereas mutations in gyrB were less frequent (30,32,33). Here the majority of mutations were found at amino acid positions 466 to 468; however, we also found two isolates with an I529V mutation, which, to our knowledge, has not been described previously.…”
Section: Resultssupporting
confidence: 80%
“…1A. In accordance with the findings of several previous studies (25,26,27,28,29,30,31), the most frequently observed mutation, T83I, was encoded in the QRDR of gyrA, whereas mutations in gyrB were less frequent (30,32,33). Here the majority of mutations were found at amino acid positions 466 to 468; however, we also found two isolates with an I529V mutation, which, to our knowledge, has not been described previously.…”
Section: Resultssupporting
confidence: 80%
“…Moreover, four of nine isolates of the former pair and 10 of 12 isolates of the latter pair also produced a CF166 A2 NM 16 4 T83I R82L A1 NM 2 1 R82L A3 M 2 1 R82L CF222 B1 NM 8 2 T83I R82L B3 NM 16 8 T83I R82L wk wk B2 M 2 2 R82L wk wk B4 M 2 0.5 wk CF86 C1 NM 4 2 D87N R82L C3 NM 16 8 T83I R82L wk detectable level of OprN or OprJ proteins related to the genes mexT (nfxC) and nfxB, respectively. Mutations in the target enzymes, DNA gyrase (gyrA) and topoisomerase IV (parC), and reduced intracellular accumulation of the drug either by decreased uptake and/or by increased efflux have been reported to be the main mechanisms of resistance to FQs in several bacterial species (1,7,10). A high level of resistance is commonly associated with gyrA and parC or two or more point mutations in the same gene or mutations involving more than one gene.…”
Section: Resultsmentioning
confidence: 99%
“…Part of the reason for the selection of gyrA mutations is probably the greater reduction in susceptibility that they afford. In P. aeruginosa, a 16-70-fold increase in MIC can be attributed to the T83I mutation (Cambau et al, 1995;Diver et al, 1991;Kureishi et al, 1994). By contrast, the transposable element mutations described by Breidenstein et al (2008) result in much more modest (2-46) increases in MIC.…”
Section: Parallel Evolution In Quinolone Resistancementioning
confidence: 84%